Towards a post-parliamentary democracy in Germany?: theoretical considerations and empirical observations on local democracy - Haus, Michael (The Rise of Interactive Governance and Quasi-Markets, 2003)
In the following sections I want to present a survey of the most important developments in German local politics during the last decade. In particular, I try to answer to the question whether each of these new developments contributes or may contribute to a transformation of the local political system which may be labelled a post parliamentary local democracy. Though the attempt is at best tentative, cursory and explorative, I hope to provide some considerations which are worth further reflection. My intention is to examine whether there are some lessons which the developments in German municipalities may teach us when we think about the question what post-parliamentary democracy could stand for — or, vice versa, if further theoretical work on the concept of post-parliamentary democracy could contribute to a better understanding about what has to be changed with regard to the municipal reform policy in Germany.